Novos complexos de Co(II) e Cu(II) com ligantes melofen: síntese, caracterização, estudo eletroquímico e aplicação na detecção simultânea de dopamina e ácido ascórbico - Nóbrega, Eryka Thamyris Damascena (2020)
In this work, the use of Meldrum’s acid as synthetic building block has investigated to obtain four melophen-type ligands (3a-d) and eight new complexes with Co(II) (4a-d) and Cu(II) (5a-d). The ligands were characterized by 1H and 13C nuclear magnetic resonance spectroscopy and infrared spectroscopy, and all data were consistent with the previously reported. The newly synthesized complexes 4a-d and 5a-d were characterized by infrared spectroscopy and elemental analysis, and all data are consistent with the suggested structures. Voltammetric behavior of the melophen-type complexes was investigated on aprotic medium (DMSO) using a glassy carbon electrode. The electrochemical behavior of these complexes has been shown to be similar to that of salophen-type complexes. Considering the use of salophen-type complexes as electron mediators in the resolution of overlapped anodic peaks, the use of an example of the melophen-type complexes as a modifier in the preparation of modified carbon paste electrode (MCPE) was evaluated to solve this type of problem in the simultaneous voltammetric detection of dopamine (DA) and ascorbic acid (AA). The effects of the modifier quantity, voltammetric technique parameters, and electrolyte pH on the AA and DA peak resolution were studied by a fractional factorial design 24-1. Once the conditions of analysis for the modified electrode were established, an effective separation between the peaks (270 mV) for these compounds was obtained. The results revealed that the voltammetric method using MCPE was useful for determining DA/AA, with detection and quantification limits are, respectively, 1.23 μmol L-1 and 4.10 μmol L-1 for DA and 2.57 μmol L-1 and 8.59 μmol L-1 for AA.